AB0488 CAN A GCA RISK STRATIFICATION SCORE BE HELPFUL IN CLINICAL PRACTICE?. (2nd June 2020) - Jasim, M.; Magan, P.; Awadalla, R.; Brindley, R.; Richards, D.; Hall, A.; Barraclough, J.; Adizie, T.
Abstract : Background: Giant cell arteritis (GCA) is the most common type of large vessel vasculitis. Typically it presents in patients over the age of 50 with a combination of temporal headaches, scalp tenderness, jaw claudication, raised inflammatory markers and visual disturbance. The diagnosis of GCA is often challenging and there is a difficult balance of over and under investigation. There have been several proposed scoring systems to help clinicians risk stratify patients who may present with suspected GCA. One such scoring system, published in 2017, showed clinical utility in a large international multi-centre study. Following analysis by logistic regression on data from 530 biopsies, Ing et al. developed a parsimonious prediction model comprising 5 candidate criteria: age, jaw claudication, ischemia-related loss of visual acuity, platelet count and logCRP (Figure 1). [1] Objectives: Increasingly, ultrasound doppler imaging is recognised and accepted as satisfactory means of confirming the diagnosis of GCA, with the presence of the halo sign characteristic for GCA. The aim of our study was to determine whether this GCA prediction model accurately predicts positive temporal artery biopsies in a large, real world UK cohort. In addition, we assessed whether this model accurately predicts positive temporal artery ultrasounds. Methods: A retrospective cohort study was performed using electronic medical records of patients referred for temporal artery biopsy (TAB) and temporal artery ultrasound (USTA) for suspected GCA. All TAB performed at the Royal Wolverhampton NHS Trust between June 2014 - June 2018 and all USTA performed between January 2015 - January 2019 were analysed. Patients who undergo USTA for suspected GCA at our centre routinely have bilateral temporal and axillary arteries scanned. Patients were excluded if they already had a previous diagnosis of GCA (and the clinical question was suspected flare), or if there was insufficient information available. Results: The total number of patients who underwent a confirmatory diagnostic test (either TAB or USTA) for suspected GCA was 187. Thirteen of these patients met the exclusion criteria, the remaining 174 patients were included for analysis. 126/174 patients underwent a TAB, 63/174 had an USTA. 15/174 had both these were included in the USS cohort because for all these patients the ultrasound was the first diagnostic test performed (Table 1 ). Our results appear to closely mirror the original multi-centre results with regards to prediction of biopsy positive GCA, with the centiles closely following those in the inception cohort. 0% of the 'low' risk probability biopsy cohort were misclassified - none had a positive biopsy. However, 8% of the 'low' risk probability ultrasound cohort were misclassified - 2 had a positive ultrasound. Conclusion: Our study, highlights that a probability score for GCA derived from a large multi-centre cohort of patients who were biopsy positive, predicts ultrasound positivity with similar accuracy. Our work reveals that scoring systems are not infallible but can be helpful in guiding clinical decision making References: [1]Ing EB, Lahaie Luna G, Toren A, et al. Multivariable prediction model for suspected giant cell arteritis: development and validation. Clin Ophthalmol . 2017;11:2031–2042. Published 2017 Nov 22. Acknowledgments: Many thanks to the Rheumatology, Opthalmology & Ultrasound teams at Royal Wolverhampton NHS Trust Disclosure of Interests: None declared